Antibacterial activity and bioactive compounds of symbiotic bacterial isolates from Polycarpa aurata in Barrang Lompo Island, Makassar, Indonesia - HERWIN HERWIN; GEMINI ALAM; SARTINI SARTINI; NURHASNI HASAN; ABDUL RAHIM; HERLINA RANTE; RISFAH YULIANTI; LATIFAH RAHMAN (Society for Indonesian Biodiversity, 2025)
Abstract. Herwin, Alam G, Sartini, Hasan N, Rahim A, Rante H, Yulianti R, Rahman L. 2025. Antibacterial activity and bioactive compounds of symbiotic bacterial isolates from Polycarpa aurata in Barrang Lompo Island, Makassar, Indonesia. Biodiversitas 26: 2339-2354. Polycarpa aurata is a marine organism capable of producing secondary metabolites from its symbiont microorganism and has therapeutic potential, such as antitumor and antimicrobial. P. aurata isolated from the symbiont bacteria obtained the AQ2-1 isolate, and secondary metabolites were produced through fermentation to obtain the AQ2-1 fermented ethyl acetate extract. The ethyl acetate extract was a bioactive compound isolated using radial chromatography and preparative thin-layer chromatography to obtain isolate 1 and isolate 2. Using ultraviolet-visible spectroscopy analysis, one-dimensional and two-dimensional nuclear magnetic resonance, and mass spectroscopy, the structure of the compound showed an adenine riboside compound (isolate 1), which has a ? max of 242 nm, 10 carbon atoms, 13 hydrogen atoms, 5 nitrogen atoms, 4 oxygen atoms, and molecular formula of C10H13N5O4, m/z 267, and Bis(2-ethylhexyl) benzene-1,2-dicarboxylate (isolate 2), which has a ? max of 218 nm, 24 carbon atoms, 38 hydrogen atoms, 4 oxygen atoms, and a molecular formula of C24H38O4, m/z 390. Based on an analysis of the biological activity of compounds 1 and 2 using bioautography thin-layer chromatography, these compounds were found to be active against Escherichia coli ATTC 25922, Salmonella typhi NCTC 786, Shigella dysenteriae ATCC 13313, Pseudomonas aeruginosa ATCC 27853, and Vibrio cholerae ATCC 25175 bacteria.